A review of the most influential research papers on COVID-19: An excerpt with comments and insights - Sinha Sudipta; Mohan Modak Nikunja; Sankar Sana Shib (Yugoslav Journal of Operations Research)
For the past two years, COVID-19 has been a global nightmare for human civilization. It genuinely poses a serious threat to public health because of its rapid proliferation. The deadly SARS-COV-2 virus is being researched on a global scale to determine its biology, origin, and potential treatment. Numerous research publications covering various aspects of the COVID-19 issue have already been published as a result of the burgeoning interest in this hot topic. The reputable and well-known search engine SCOPUS is used to compile crucial information. In order to emphasize a thorough and extensive assessment of research output using COVID-19 publications, we looked at 100 research and review papers that received the majority of citations. It discovers a list of keywords that appear more than 14 times. It can be seen that the terms "Human/ Humans," "Coronavirus Disease 2019," "Coronavirus Infection/Coronavirus Infections," "Pneumonia viral," and "Virus pneumonia" held the top five positions. The New England Journal of Medicine is in the first place, having published 15 research papers delineating different features of SARS-CoV-2. In addition to this, a significant number of publications connected to the Covid-19 issue were also published in "The Lancet," "Nature," "JAMA Journal of the American Medical Association," and "Cell." Regarding papers published on COVID-19, China is also performing well. The USA and the UK placed second and third, respectively, in terms of the quantity of Covid-related articles published. This work outlines a detailed global research scenario of COVID-19 describing its origin, nature, identification, way of entry in a human cell, symptoms of the infected patients, way of prevention, fatal effects on comorbid and aged patients with the help of correlation between comorbidity and mortality, the effect of on newborn baby and children, the emergence of telemedicine, persistence of the virus on inanimate things, the efficacy of drugs like remdesivir, lopinavir, ritonavir and so on, the progress of vaccine development, usefulness gloves, masks, sanitizer, the advantage of maintaining physical and social distance, infrastructure development. Finally, we conclude by summarizing the main points of the 100 research papers, which will undoubtedly aid in identifying the research gap and future research directions.